2021
DOI: 10.1519/jsc.0000000000003283
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Static and Dynamic Stretching Performed Before Resistance Training on Muscle Adaptations in Untrained Men

Abstract: Effects of static and dynamic stretching performed before resistance training on muscle adaptations in untrained men. J Strength Cond Res 35(11): 3050-3055, 2021-This study evaluated the effects of dynamic and static stretching (SS) performed before resistance training on biceps femoris hypertrophy and knee flexor strength gains in untrained young men. Forty-five untrained young men (age, 21.2 6 0.5 years; mass, 72.2 6 5.6 kg; height, 178 6 1 cm) were randomly assigned to 1 of the 3 groups: (a) 80 seconds of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 40 publications
0
26
0
2
Order By: Relevance
“…Compared with a third group, which performed only bouts of resistance exercise (i.e., non‐stretch control group), stretch training groups demonstrated no impairments in biceps femoris growth after the 8‐week training period. Also, in this case, performing stretching did not diminish the total resistance training volume (Ferreira‐Júnior et al, ). Conversely, Kubo et al () found that performing stretching twice daily 5 × 45 s did not impair the hypertrophic response when combined with resistance training (unilateral plantar flexion at 70% of 1RM with 5 × 10 repetitions, 4 sessions/week) compared with a resistance training‐only protocol (2.9% vs. 3.1% for resistance training and resistance + stretch training, respectively).…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Compared with a third group, which performed only bouts of resistance exercise (i.e., non‐stretch control group), stretch training groups demonstrated no impairments in biceps femoris growth after the 8‐week training period. Also, in this case, performing stretching did not diminish the total resistance training volume (Ferreira‐Júnior et al, ). Conversely, Kubo et al () found that performing stretching twice daily 5 × 45 s did not impair the hypertrophic response when combined with resistance training (unilateral plantar flexion at 70% of 1RM with 5 × 10 repetitions, 4 sessions/week) compared with a resistance training‐only protocol (2.9% vs. 3.1% for resistance training and resistance + stretch training, respectively).…”
Section: Discussionmentioning
confidence: 87%
“…In an effort to provide additional insights on the topic, several studies have endeavoured to determine how stretch training impacts hypertrophy in conjunction with regimented resistance training (Evangelista et al, 2019;Ferreira-Júnior et al, 2019;Kubo, Kanehisa, & Fukunaga, 2002b;Moriggi Junior, Berton, Souza, Chacon-Mikahil, & Cavaglieri, 2017;Silva et al, 2014; Table 3). For example, Moriggi Junior et al…”
Section: Discussion and Con Clus I On Smentioning
confidence: 99%
See 3 more Smart Citations